Answer :

P = –(x – 2)

Q = –2(y +1) 

R = –x + 2y,

According to question P + Q + R = ax.

- (x – 2) –2(y +1) –x + 2y = ax


= -x +2 -2y – 2 -x + 2y = ax


= -2x = ax


= a = -2

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
RELATED QUESTIONS :

Add the followingNCERT - Exemplar Mathematics

<span lang="EN-USNCERT Mathematics

(a) What should bNCERT - Exemplar Mathematics

Subtract

<
NCERT - Exemplar Mathematics

Subtract 9a2NCERT - Exemplar Mathematics

To what expressioNCERT - Exemplar Mathematics

(a) What should bNCERT - Exemplar Mathematics

State whether theNCERT - Exemplar Mathematics

How much is y<supNCERT - Exemplar Mathematics

How much is 21a<sNCERT - Exemplar Mathematics